'Some parts of the consent form are written using complex scientific language’: community perspectives on informed consent for research with pregnant and lactating mothers in Uganda - Adelline Twimukye; Sylvia Nabukenya; Aida N. Kawuma; Josephine Bayigga; Ritah Nakijoba; Simon Peter Asiimwe; Fredrick Byenume; Francis Williams Ojara; Catriona Waitt (BMC Medical Ethics)
Abstract Background Appropriate language use is essential to ensure inclusion of diverse populations in research. We aimed to identify possible language-related barriers regarding the informed consent process and propose interventions to improve clarity and understanding of pregnant and breastfeeding women participating in research. Methods A cross-sectional qualitative study employing focus group discussions (FGD) was conducted in Uganda from August 2023 to September 2023, involving a diverse group of stakeholders from the community, including community members, research participants, and Community Advisory Board members. 19 FGD comprised adult participants representing at least six different mother tongues (Luganda, Acholi, Runyankole, Runyoro, Lugbara and English). An inductive thematic approach was utilized for data analysis using NVivo version 12 software to identify language factors that influence informed consent. A series of community validation workshops ensured concurrence. Results At the individual level, language barriers, and low levels of literacy contributed to poor comprehension, thus hindering ability to achieve genuine informed consent. At the health facility level, participants reported that there was use of inappropriate, unclear language including inaccurate translations, with poor and complicated grammar in some consent forms. Participants reported that complex medical terminologies are difficult to translate to local languages. Community members highlighted that social/cultural norms in language use affected cultural perceptions of informed consent. To enhance understanding for individuals without education in science, participants suggested simplification of terminologies and avoidance of complex medical jargon. Researchers should identify participants’ preferred languages and communicate in those languages whenever possible. If researchers are not fluent, trained interpreters should be identified. Informed consent documents must be translated into local languages to ensure participants comprehend the study’s purpose, procedures, risks, and benefits. Involving community members during development and translation of these documents can provide valuable insights into local dialects and culturally specific concepts, ensuring that study tools like surveys and consent forms are accurate and respectful. Conclusion Language barriers influence the informed consent process within communities in Uganda. These can potentially be resolved at individual, health system and community levels. Consideration of locally understandable terms in community-facing study documentation is likely to enhance understanding and could improve research participation, although further studies are needed to assess these. The use of appropriate language ensures that informed consent is genuine in keeping with principles of Good Clinical Practice, and developing a research communication strategy should be part of inclusive research design.